USE OF LAW BREDFORD FOR DETERMINATION OF QUANTITY OF ACQUIRED EDUCATIONAL CONCEPTS AT THE LESSONS - Mykhailo H. Koliada (Інформаційні технології і засоби навчання, 2014)
In the article one of likelihood laws of distribution as a universal remedy of knowledge and transformation of the pedagogical validity is considered. It is shown that model which is based on processing of the information received at the lesson, creates information display of the main pedagogical factors, principles and laws. The article aims to display the use of the Law Bredford for determination of quantity of acquired educational concepts at the lessons taking into account criterion of their value. It is revealed that this law gives the chance not only to allocate scientifically zones of the importance of educational concepts which are studied at the lessons, but also to calculate their interdependent quantitative structure.